Another British disease? A recent increase in the prevalence of psychiatric morbidity. Issue 5 (October 1993) - Lewis, G; Wilkinson, G
Abstract : AIMS AND OBJECTIVE–To examine trends in the prevalence of psychiatric morbidity in Britain between 1977 and 1985. DESIGN–Secondary analysis of two cross sectional population based surveys. SETTING–The first survey was conducted in 1977 in West London and the second in 1984-85 throughout Great Britain. PARTICIPANTS–Members of the public randomly selected from the electoral register. MEASUREMENTS AND MAIN RESULTS–The main outcome was the prevalence of psychiatric morbidity assessed using the General Health Questionnaire, a self administered measure of neurotic symptoms. There was an increase of at least 8% (95% confidence interval 6.6, 9.8) in the prevalence of psychiatric morbidity between the times of the two surveys and this difference persisted after adjustment for any changes in the sex, age, employment status, marital status, social class, and housing tenancy between the two samples. When the analysis was restricted to the Greater London respondents of the Health and Lifestyle Survey a larger increase in psychiatric morbidity was seen. CONCLUSIONS–It is likely that there was an increase in the prevalence of psychiatric morbidity in Great Britain between these two surveys. Psychiatric morbidity is a public health problem of some importance and the causes of this increase require further study.